Cover Feature: Electrolyte Effects on the Stability of Ni−Mo Cathodes for the Hydrogen Evolution Reaction (ChemSusChem 15/2019). Issue 15 (1st August 2019) - Wijten, Jochem H. J.; Riemersma, Romy L.; Gauthier, Joseph; Mandemaker, Laurens D. B.; Verhoeven, M. W. G. M. (Tiny); Hofmann, Jan P.; Chan, Karen; Weckhuysen, Bert M.
Abstract : The Cover Feature shows how molybdenum leaches from the nickel–molybdenum electrocatalysts used for the hydrogen evolution reaction. Molybdenum leaching primarily occurs under the influence of hydroxyl anions, but it is also a function of the counter cation (e.g. Na +, K +, and Li + ) used during electrocatalysis. The accompanied increase of the catalyst surface area results in an increased electrocatalytic efficiency. More information can be found in the Full Paper by J. H. J. Wijten et al. on page 3491 in Issue 19, 2015 (DOI: 10.1002/cssc.201900617 ).